THE MEUSEURAYA CULTURE IN AGRICULTURE: A CASE STUDY IN REUSEB VILLAGE, PIDIE JAYA - Asmanidar, Asmanidar (Jurnal Sosiologi Dialektika Sosial, 2024)
This study aims to explore the cultural practice of Meuseuraya (mutual cooperation) in Desa Reuseb, Kecamatan Trienggadeng, Kabupaten Pidie Jaya, analyzing its evolution from a cornerstone of community engagement to its present-day decline amidst modernization and technological advancements. Employing qualitative research methods, this study collected data through interviews, observation, and documentation in Desa Reuseb. Informants, including local leaders and community members, were selected using purposive sampling. The data was then analyzed using qualitative descriptive techniques, focusing on the interactive model of analysis. Historically, Meuseuraya played a vital role in fostering community spirit and cooperation in agricultural and social activities within Desa Reuseb. It was integral to community bonding and supported various communal tasks, such as building infrastructure and farming. However, the study reveals a significant decline in the practice due to modernization, technological adoption in agriculture, and changing lifestyle preferences among the community. The fading practice of Meuseuraya represents a loss of cultural heritage and community spirit in the face of modern challenges. Despite these changes, the values underlying Meuseuraya remain crucial for fostering community solidarity and identity. This study concludes that revitalizing and adapting Meuseuraya to contemporary conditions could help preserve its cultural significance and enhance community resilience and sustainability. Future initiatives should focus on integrating traditional cooperation techniques with modern agricultural practices to maintain the relevance and benefits of Meuseuraya in current and future generations.